İslam Hukuku ve Uluslararası Hukukta Esir Hakları - Mohammed Abdo, Fawaz (Muş Alparslan Üniversitesi, 2021)
One of the most important aspects of Islamic fiqh since its inclusion in the historical process is the issue of rights. Especially in times of war and peace, human rights have an important place in the fiqh literature. During war, man can lose his freedom, be persecuted, mistreated or imprisoned. For this reason, Islam has determined the rights, duties and rules that should be taken into account regarding the good treatment of captives. If we look at history, we come across dark practices regarding savings for captives. Because we can see that the prisoners are subjected to physical torture such as beating, wounding, harassment and burning as long as they remain in the hands of the enemy. Again, we understand from the practices of the pre-Islamic period of Jahiliyyah that the prisoner was deprived of eating and drinking, punished with hunger and thirst, and left to die. In both Islamic law and civil law, various articles and provisions have been adopted on the subject of captives. In the context of Islamic law, different views have been put forward regarding the exchange and killing of prisoners. Among the schools of fiqh, there are those who find their killing wrong, as well as those who evaluate the issue in the context of the country's interest. In our study, it is aimed to illuminate the discussions on the subject in Islamic law to some extent, and the references of the current international treaties to the prisoner law in wars are mentioned.

İslam fıkhının tarih sürecine dahil oluşundan beri en önemli yanlarından biri haklar konusudur. Özellikle savaş ve barış zamanlarında insan hakları fıkıh literatüründe büyük bir yer kaplamıştır. İnsan, savaş sırasında özgürlüğünü kaybedebilir, zulüm ve kötü muamele görebilir veya hapse atılabilir. Bu nedenle, İslam esirlere iyi davranılması hususunda dikkate alınması gereken hak, görev ve kurallar belirlemiştir. Tarihe bakacak olursak esirlere yönelik tasarruflar konusunda karanlık uygulamalara rastlamaktayız. Çünkü esirlerin düşman elinde kaldığı sürece insan değerlerini ihlal eden muamelelerle karşılaştığı, dövme, yaralama, taciz, yakma gibi fiziksel işkenceye maruz kaldığını görebilmekteyiz. Yine esirin yeme ve içmeden mahrum bırakılarak, açlık ve susuzlukla cezalandırılıp ölüme terkedildiğini İslam öncesi cahiliye dönemi uygulamalarından anlamaktayız. Esirler konusunda gerek İslam hukukunda gerekse sivil hukukta çeşitli maddeler ve hükümler benimsenmiştir. İslam hukuku bağlamında esirlerin takas edilmesi ve öldürülmesine ilişkin farklı görüşler ortaya konmuştur. Fıkıh ekolleri arasında onların öldürülmesini yanlış bulanlar olduğu gibi konuyu ülkenin çıkarı bağlamında değerlendirenlere de rastlanmıştır. Çalışmamızda İslam hukukunda konuya ilişkin tartışmaları bir nebze aydınlatmak gayesi güdülmüş, yürürlükteki uluslararası antlaşmaların savaşlardaki tutsak hukukuna ilişkin atıflarına değinilmiştir.
Right of Prisoners in Islamic and International Law
dinbil
Keywords: Islamic Law; Captive; Rights; Law; International Law; İslam Hukuku; Esir; Haklar; Hukuk; Uluslararası Hukuk